Bone Mineral Density Measurement in Menopausal Women Presenting with Low Back Pain: A Prospective Study - Ansari, Selim M; Begum, T; Siddique, AB (TAJ: Journal of Teachers Association, 2009)
Bone mineral densitometry was done in 107 women in their post-menopausal period using Dual energy X-ray absorptiometry method. All the patients were presented with low back pain. Quantification of bone mineral density was done in proximal femur and lumber spines of all the patients. Sixty-eight patients showed normal bone mineral density in our study. Rest 39 patients showed declination of bone mineral density from mild osteopenia to severe osteoporosis. We conclude that Dual energy X-ray absorptiometry bone mineral measurement is an unique, noninvasive method of detecting bone mass disorder in post-menopausal women with low back pain and should be the first choice of investigation. doi: 10.3329/taj.v15i2.3909 TAJ December 2002; Vol.15(2):64-67